Chewing chitosan-containing gum effectively inhibits the growth of cariogenic bacteria - Hayashi, Yoshihiko; Ohara, Naoko; Ganno, Tomoko; Yamaguchi, Keiji; Ishizaki, Takahide; Nakamura, Taisuke; Sato, Makoto (Archives of oral biology, 2007)
We have already reported that chitosan inhibited the growth of cariogenic bacteria in vitro. This study was designed to evaluate whether chewing gum, containing chitosan, can effectively suppressed the growth of oral bacteria (total bacteria, total Streptococci, mutans streptococci (MS)) in saliva. Fifty healthy subjects, ranging in age from 19 to 32 years, were recruited from among the staff and students of Nagasaki University School of Dentistry. For the slab of gum study, the subjects chewed gum for 5 min and then rested for 5 min. Each subject chewed a total of eight pieces of gum, which was either supplemented with or without chitosan, for a total of 80 min. Two different types of gums were examined with at least 1 week as a rest period in between treatments. This in vivo study was carried out by the double blind comparison test. The amount of oral bacteria was found to significantly decrease in the chitosan group. Especially, the number of MS were maintained at about a 20% level in comparison to that before gum chewing, even at 1 h after gum chewing. These findings suggest that a supplementation of chitosan to gum is an effective method for controlling the number of cariogenic bacteria in situations where it is difficult to brush one's teeth, such as when an individual is away from home all day or participating in outdoor training.